Business. One: One. Advanced teacher's book - Appleby R. Rachel; Bradley J. John; Leeke N. Nina; Scrivener J. Jim (Oxford Business English)
Business one:one is the first business English course written specifically for teaching and learning one-to-one. Its non-linear approach allows you to negotiate with your student what the course covers, what happens in each lesson, and how they practise between lessons. What does your student want from the course? Use the free MultiROM to help your student select the topics they need to cover from the How to ... course syllabus.Then use the interactive Learning planner to create a personalized course plan. What do you do in the lesson? The 45-60 minute lesson starts with the target language. Negotiate with your student what happens next. Choose from: communicative tasks like speaking or writing, discussing grammar or collocations in the Language box, talking through helpful ideas in the Hint section. Encourage your student to use the Lesson record to collate the most useful language from each lesson. It's easy to look it up at any time.